2004
DOI: 10.1161/01.atv.0000117200.46938.e7
|View full text |Cite
|
Sign up to set email alerts
|

Telomere Shortening in Human Coronary Artery Diseases

Abstract: Background-Increased cell turnover in response to injury is considered to be important in the development of atherosclerotic plaques. Telomere shortening has been shown to be associated with cell turnover. We assessed the telomere length of human coronary endothelial cells to clarify whether there is a relationship between telomere shortening and coronary artery disease (CAD). Methods and Results-Coronary endothelial cells were obtained from 11 patients with CAD who underwent autopsy and 22 patients without CA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
156
0
5

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 239 publications
(170 citation statements)
references
References 40 publications
9
156
0
5
Order By: Relevance
“…These findings have been confirmed in other cohorts of patients with coronary disease [59,62]. Not only are WBC telomeres shorter, but telomeres of coronary artery endothelial cells of atherosclerotic plaques are also shorter compared to non-atherosclerotic segments and healthy controls [60].…”
Section: Atherosclerosissupporting
confidence: 65%
See 1 more Smart Citation
“…These findings have been confirmed in other cohorts of patients with coronary disease [59,62]. Not only are WBC telomeres shorter, but telomeres of coronary artery endothelial cells of atherosclerotic plaques are also shorter compared to non-atherosclerotic segments and healthy controls [60].…”
Section: Atherosclerosissupporting
confidence: 65%
“…In addition to the association between telomeres and the risk factors for atherosclerosis, a relationship between telomeres and atherosclerotic disease itself has also been observed [23,[59][60][61][62]. WBC telomere length in patients who had a myocardial infarction before the age of 50 years was shorter than in healthy controls, independently from other atherosclerotic risk factors [23].…”
Section: Atherosclerosismentioning
confidence: 97%
“…A previous study demonstrated that patients with CVD had shortening of total telomere length compared with healthy participants (21). Notably, previous reports have found that total telomere shortening per se causes cellular senescence in vascular endothelial cells (22) and eventually leads to atherosclerotic plaques (23).…”
Section: Discussionmentioning
confidence: 98%
“…Кроме того, короткие теломеры ассоции-руются с повышенным риском развития ССЗ. В част-ности, ассоциативные связи прослеживаются меж-ду короткими теломерами и АГ [31], хронической сердечной недостаточностью [36], атеросклерозом [37].…”
Section: эффекты низкосолевой диеты на молекулярно-генетическом уровнеunclassified